Agrobacterium rhizogenes mediated genetic ransformation in Koduveli (plumbago spp. Linn.) - Roshna Bhaskar (Department of Plant Biotechnology, College of Agriculture, 2006)
Investigations on “Agrobacterium rhizogenes mediated genetic transformation in Koduveli (Plumbago spp. L.)” were carried out at the Department of Plant Biotechnology, College of Agriculture, Vellayani during 2003-2006. Two plant species viz., Plumbago zeylanica and Plumbago rosea having great medicinal value by virtue of plumbagin, a naphthoquinone, present in them were selected for the study. Standardisation of rapid in vitro propagation of these medicinal plants was attempted in the present study.